2013
DOI: 10.1186/1746-6148-9-93
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the biofilm forming ability of Staphylococcus pseudintermedius from dogs

Abstract: BackgroundStaphylococcus pseudintermedius is an opportunistic pathogen of dogs and has emerged as a leading cause of skin, wound and surgical site infections worldwide. Methicillin resistance is common and clinical infections as a result of methicillin-resistant S. pseudintermedius (MRSP) pose a clinical challenge. In other staphylococci, biofilm formation has been shown to be a virulence factor for infection, however, it has received little attention in S. pseudintermedius. The objectives of this study were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
87
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(107 citation statements)
references
References 31 publications
10
87
2
8
Order By: Relevance
“…Yet, the study failed to find differences in the biofilm formation between MRSP and MSSP isolates. The number of MSSP isolates that was studied was low, and the authors suggested that further experiments with a larger number of isolates were warranted (6). By using a larger set of isolates, we observed that biofilm production in the BHIB and BHIB-1% glucose media was significantly higher in MSSP than in MRSP isolates.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Yet, the study failed to find differences in the biofilm formation between MRSP and MSSP isolates. The number of MSSP isolates that was studied was low, and the authors suggested that further experiments with a larger number of isolates were warranted (6). By using a larger set of isolates, we observed that biofilm production in the BHIB and BHIB-1% glucose media was significantly higher in MSSP than in MRSP isolates.…”
Section: Discussionmentioning
confidence: 59%
“…This capacity might further complicate the treatment of already challenging infections due to the decrease in effectiveness of antimicrobials on biofilms (5). In one study, all S. pseudintermedius isolates produced biofilms, suggesting that biofilm production might be essential for the pathogenicity of S. pseudintermedius (6). Yet, the study failed to find differences in the biofilm formation between MRSP and MSSP isolates.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Among staphylococci, Staphylococcus epidermidis is widely known as the predominant cause of biofilminduced catheter-and medical device-related sepsis in humans (O'Gara & Humphreys 2001). Recently, several studies reported that MRSP, especially sequence type (ST) 71, also has an ability to produce biofilms, suggesting the necessity of investigation for the prevalence of biofilm-producing S. pseudintermedius in veterinary practices (Dicicco et al 2012;Osland et al 2012;Singh et al 2013). In South Korea, several studies have reported a high prevalence of MRSP in dogs Yoon et al 2010).…”
Section: Introductionmentioning
confidence: 99%